Can we use the neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and mean platelet volume values for the diagnosis of anterior uveitis in patients with Behcet’s disease? - Avci, Atil (Ther Clin Risk Manag, 2017)
INTRODUCTION: The purpose of this study was to compare the value of hematological parameters, neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and mean platelet volume (MPV), as indicators of anterior uveal segment involvement in patients with Behcet’s disease (BD). PATIENTS AND METHODS: Hospital-based records of a total of 912 patients with BD from the dermatology clinic and healthy volunteers from the checkup clinic were assessed retrospectively. After applying the exclusion criteria of the study, 71 of the BD patients with anterior uveitis, 69 of the BD patients without ophthalmological pathology and 151 healthy volunteers were included in the study. MPV, PLR, and NLR values of patients and healthy volunteers were compared. RESULTS: All MPV, PLR, and NLR values of patients who had anterior uveitis were significantly higher than those of other patients and healthy volunteers. Statistically, considering area under curves (ratio): NLR was 0.725 (0.653–0.797), P<0.001; PLR was 0.600 (0.523–0.676), P=0.012, and MPV was 0.358 (0.279–0.437), P<0.001. CONCLUSION: MPV, PLR, and NLR are all valuable for assessment of anterior uveal segment involvement in patients with BD. However, the NLR seems to be better than the PLR and MPV for indicating anterior uveitis due to BD.